Finite-element modelling of acoustic wave scattering from fluid, rigid and elastic objects - Falou, Omar; Kumaradas, J. Carl; Kolios, Michael C. (Canadian Acoustics, 2005)
A finite element model (FEM) of acoustic wave propagation through 3-D arbitrary-shaped structures is developed to solve the problem of high frequency acoustic scattering. The FEMLAB&reg software package was used to develop and solve acoustic scattering models from fluid, rigid, and elastic spheres immersed in a fluid medium, for which analytical solutions are available. The entire computation domain is modeled as a sphere filled with fluid domains. It is found that the FEM provided accurate predictions of wave scattering by three types of scatterers, fluid, rigid immovable, and elastic.